2014
DOI: 10.12691/jfnr-2-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of CHIA (<i>Salvia hispanica L.)</i> for Use in Food Products

Abstract: Chia is a seed native to the region that extends from the North of Mexico to Guatemala, and it has been target of study for food enrichment. Many of its newly developed functional foods contain bioactive compounds including dietary fiber, antioxidants and other substances. The objective of this study was to evaluate chia seed (Salvia hispanica L) from her chemical components and prove their claim for functional properties. Chia seeds contain high levels of lipids (34.4%) and are rich in Omega-3, Omega-6 and Om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
34
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(45 citation statements)
references
References 22 publications
9
34
1
1
Order By: Relevance
“…Furthermore, our results are in line with many reports of Chia oil content in areas of origin, ranging from 20.30 to 38.60 % [4,5,[37][38][39]. Oil yield can be affected by extraction technique; for example, Ixtaina el al.…”
Section: Chia Seeds Qualitysupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, our results are in line with many reports of Chia oil content in areas of origin, ranging from 20.30 to 38.60 % [4,5,[37][38][39]. Oil yield can be affected by extraction technique; for example, Ixtaina el al.…”
Section: Chia Seeds Qualitysupporting
confidence: 91%
“…However, to have an effective antioxidant activity, a ratio of tocopherols (mg %) to polyunsaturated fatty acids (g%) > 0.8 should be found [45], whereas in Chia seeds it was about 0.6. Total polyphenols were not significantly different between OM and Pe, whereas Au sample had higher [39], but slightly lower than those reported by other authors [9,38]. All treatments differed in antioxidant activity (p < 0.05), evaluated by ABTS ·+ radical-scavenging assay.…”
Section: Chia Seeds Qualitycontrasting
confidence: 59%
“…In agreement with several authors, DC was better than DE because chia is a very rich source of minerals, protein, dietary fiber, and lipids (Ayerza, ; Bushway, Belyea, & Bushway, ; Silveira Coelho & Salas‐Mellado, ). In fact, the nutritional composition of the CS used was similar to other reports, although the lipids content was slightly lower in respect to the average value of 31.11 g/100 g (Bushway et al, ; da Silva et al, ; Romankiewicz et al, ; Silveira Coelho & Salas‐Mellado, ) As expected, most of the fatty acids found in DC and in CS corresponded to those reported in the literature and their amounts (Ayerza, ; Gutiérrez‐Tolentino et al, ; Romankiewicz et al, ; Silveira Coelho & Salas‐Mellado, ); however, this is the first report of butyric acid in a chia‐enriched diet. As butyric acid was not detected in CS, this was probably produced in DC because it is one of the main products of fiber and protein degradation, which are found in high amounts in chia; importantly, butyric acid possesses beneficial metabolic effects and prevents NAFLD (Juárez‐Hernández et al, ; Lyu et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, the TPC of DE resulted 11.6‐fold higher than the only one TPC value reported in literature for a rat standard diet (0.59 mgGAE/g) (Vardi, Parlakpinar, Ates, Cetin, & Otlu, ). Besides, data from literature for the TPC of CS report values ranging from 0.642 to 5.78 mg GAE /g, while the value of 4.54 ± 0.11 mg GAE /g obtained in this study is similar to the highest one in the range (Martinez‐Cruz & Paredes‐Lopez, ; Romankiewicz et al, ; Silveira Coelho & Salas‐Mellado, ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation